Short Communication: Growth performance, and blood profile of kampong chicken fed diets containing Moringa oleifera powder and liquid (Asian Journal of Agriculture, 2020)
Abstract. Adli DN. 2020. Short Communication: Growth performance, and blood profile of kampong chicken fed diets containing Moringa oleifera powder and liquid. Asian J Agric 4: 83-86. The research purpose is to carry out the possible effect of Moringa oleifera on Growth performance, and intestinal properties of Lohmann broiler. 80 one-day-old kampongs were randomly allocated to 4 dietary treatments and 4 replicates of 5 birds per cage. Four treatments used for research were dietary with control (T0), basal diet + M. oleifera 80 g (T1), Drinking water + 2 mL/L M. oleifera (T2), and basal feed + M. oleifera 80 g+ drinking water 2 mL/L M. oleifera (T3). The results showed that using M. oleifera presented no significant difference (P < 0.05) on body weight gain at 1-35 days and intestinal properties. The microstructure didn't affect negatively to its structure. In conclusion, addition of M. oleifera does not impact growth performance, and but can reduce amount of glucose in kampong chicken.
Keywords: Blood biochemistry, Kampong chicken, Performance